The Influence Of Leadership And Work Facilities On Employee Performance At Bank Bri Manna Branch, South Bengkulu District - Arles, Fran; Susena , Karona Cahya; Abi , Yudi Irawan (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
Banks are companies where people borrow and save money. With banks, human resources must be more professional in managing finances. Human resources are the people who design and formulate all organizational strategies and goals. Without people who have expertise or competence, it is impossible for an organization to achieve its goals. The sample in this research was all BRI Manna Branch Employees, South Bengkulu Regency, totaling 67 people. The results of the multiple linear regression analysis are the equation: Y = 10.904 + 0.334 X1 + 0.423 at BRI Manna Branch, South Bengkulu Regency The value of the coefficient of determination using SPSS 23.00 can be seen from the coefficient of determination from R square of 0.662. This means that the Leadership value (X1) and Work Facilities value (X2) influence Employee Performance (Y) by 66.2.0% while the remaining 33.8% is influenced by other variables not examined in the research. The results of the t test at a significance level of 0.05 explain that partially leadership and work facilities have a significant influence on employee performance at BRI Manna Branch, South Bengkulu Regency. The results of the f test at a significance level of 0.05 explain that leadership and work facilities have a significant simultaneous influence on employee performance at BRI Manna Branch, South Bengkulu Regency.